Clinical and morphological stages of bone fragments fusion - Popsuishapka, Olexii; Litvishko, Valeriy; Ashukina, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Bone regeneration is a cascade of cellular and molecular phenomena leading in the fracture region to the formation of bone tissue which is identical to the original one. The process is divided into stages between which it is impossible to draw a clear line. Objective: To identify key clinical and morphological phenomena that define the staging process of fragments fusion after the bone fracture, to clarify the essence of the first stage, to set the dates of each stage in humans. Methods: Experiments were performed in 8 adult Karakul breed sheep weighing 35–40 kg underwent a closed fracture of the right femur. Plot fracture examined by histological methods after 5 hours, 1, 4 and 15 days. Near fragmental space studied in 43 patients with closed fractures of long bones which was performed open reduction of bone fragments in. Retrospectively we evaluated clinical data in 546 patients with diaphyseal fractures of the extremities accumulated over the past 30 years. Results: it is proved that the fibrin blood clot is naturally necessary structure for proliferation and differentiation of cells and for the formation of new bone tissue. After ultrasound examination it was found that the shape and location of bone regenerate conforms to the shape and location of the fibrin blood clot. Based on the study of angular mobility of bone fragments and bone regenerate formation we established terms of healing of fractures in humerus in the period from 4 to 8 weeks, in femur — from 8 to 12, and in shin bones — from 8 to 17 weeks. Conclusion: There were proposed to highlight formation of a fibrin blood clot as the first important step of bone regeneration which completely or partially fills near fragmental space. Approximate lifetime formation and stabilization of its structure is from 12 to 24 hours. There were established terms of the stages of healing of diaphyseal fractures in human long bones.